Drinking Water Supply System (SPAM) and Reservoir Planning in Dusun Lebaho Lais - Adelia Farahdita Maharani; Viva Oktaviani; Suharto Suharto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Clean water availability is a fundamental requirement for human life and socio-economic development, particularly in rural areas that have not been adequately served by drinking water supply systems. Dusun Lebaho Lais, located in Jembayan Dalam Village, Loa Kulu District, faces challenges in accessing sufficient and sustainable clean water due to population growth and limited infrastructure. This study aims to analyze population growth, estimate future clean water demand, and determine the required reservoir capacity to support the planning of a Drinking Water Supply System (SPAM) in the area. The research applied a quantitative descriptive method using both primary and secondary data. Primary data were obtained through direct field observations, while secondary data were collected from village records, government agencies, statistical reports, and relevant literature. Population projection was conducted using the Arithmetic Method based on population data from 2015 to 2024, with projections extended to 2035. The suitability of the projection method was evaluated using standard deviation and correlation coefficient analysis. The results show that the Arithmetic Method produced a standard deviation value of 81.747 and a correlation coefficient of 1, indicating a perfect positive correlation and high reliability. The population of Dusun Lebaho Lais was recorded at 4,544 persons in 2024 and is projected to increase to 4,858 persons by 2035, with an average annual growth rate of 1%. Based on rural water consumption standards, the projected clean water demand in 2035 is estimated at 242,889 liters per day or 242.889 m³/day. The reservoir capacity analysis indicates that a reservoir with a volume of 84.86 m³, a diameter of 6 meters, and a height of 3 meters, requiring only three reservoir units, are sufficient to support the projected water demand. These findings confirm that the planned reservoir design can adequately meet future clean water needs and support sustainable water supply development in Dusun Lebaho Lais.